A new tarantula genus, Psednocnemis, from West Malaysia (Araneae: Theraphosidae), with cladistic analyses and biogeography of Selenocosmiinae Simon 1889 - West, Rick C.; Nunn, Steven C.; Hogg, Stephen (Zootaxa, 2012)
The selenocosmiine genus Psednocnemis gen. nov. is described from the Sundaland region of South-east Asia. The typespecies Psednocnemis davidgohi sp. nov., which the male was incorrectly identified as Coremiocnemis hoggi West &Nunn 2010, is herein described. Cladistic analyses of 46 morphological characters and 39 exemplar taxa from 12 generawere done. The genera analysed were: Reichlingia Rudloff 2001; ingroup: Chilobrachys Karsch 1891; CoremiocnemisSimon 1892; Haplocosmia Schmidt & von Wirth 1996; Lyrognathus Pocock 1895; Orphnaecus Simon 1892; PhlogiellusPocock 1897; Poecilotheria Simon 1885; Psednocnemis gen. nov.; Selenobrachys Schmidt 1999; Selenocosmia Ausserer1871 (in part: Sundaland fauna only); Yamia Kishida 1920. The results presented Psednocnemis gen. nov. as monophyleticbased on presence of a distal embolic spiral curl in males and presence of a distodorsal spiniform brush on the retrolateralsurfaces of coxa IV, as well as the reduction in density of hair type 4, located along the proximoventral abdomen of bothsexes. Two new tribes are described: Chilobrachini trib. nov. and Phlogiellini trib. nov., based upon basal nodes with stron-gest branch support that best reflected natural groups. Selenocosmiini Simon 1889 and Poecilotheriini Simon 1889 arerevised and redescribed. Yamia Kishida 1920 is placed into junior synonymy of Phlogiellus (syn. nov.); ChilocosmiaSchmidt & von Wirth 1992 and Selenobrachys Schmidt 1999 are placed into junior synonymy of Orphnaecus (syn. nov.);Selenocosmia xinping Zhu & Zhang 2008 is transferred to Phlogiellus, makng the new combination Phlogiellus xinping(Zhu & Zhang 2008) comb. nov.; Selenocosmia dichromata (Schmidt & von Wirth 1992) is transferred to Orphnaecus,making the new combination Orphnaecus dichromata (Schmit & von Wirth 1992) comb. nov.; Coremiocnemis brachyra-mosa West & Nunn 2010, Coremiocnemis gnathospina West & Nunn 2010, Coremiocnemis jeremyhuffi West & Nunn2010 and Selenocosmia imbellis (Simon 1891) are transferred to Psednocnemis gen. et comb. nov. Poecilotherinae(Schmidt 1995) is no longer considered a valid subfamily and is replaced into Selenocosmiinae as the tribe Poecilotheriini.Chilocosmia barensteinerae Schmidt et al. 2010 is considered a Selenocosmiinae species incertae sedis. Ischnocolellasenffti Strand 1907 is considered a nomen dubium. All other genera examined were retrieved as monophyletic in the firstcladistic analyses exclusive to Selenocosmiinae genera (Australo-Papuan selenocosmiines are outside the scope of thiswork and are not considered). Biogeography of all Selenocosmiinae is discussed; the group is a potential model North Gondwanan taxon. A key to Psednocnemis species is provided.